2010
DOI: 10.3109/13668250.2010.499101
|View full text |Cite
|
Sign up to set email alerts
|

Maternal parenting stress in families with a child with Angelman syndrome or Prader–Willi syndrome

Abstract: In AS professional family support is essential, since parenting is stressful for many mothers. In PWS, this is especially the case when behavioural problems are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
2
29
0
2
Order By: Relevance
“…Studies about parental stress are very limited. One study described that parents of children with PWS are mostly stressed in case of behavioral problems (Wulffaert et al, 2010) and had more somatization, phobic anxiety, obsessive compulsion, and anxiety problems than parents of healthy children who were matched in age, gender and IQ (Skokauskas et al, 2012). Therefore, support for parents should incorporate knowledge about the delay of adaptive functioning in children with PWS and the consequences in daily life.…”
Section: Results In Relation To Previous Researchmentioning
confidence: 98%
“…Studies about parental stress are very limited. One study described that parents of children with PWS are mostly stressed in case of behavioral problems (Wulffaert et al, 2010) and had more somatization, phobic anxiety, obsessive compulsion, and anxiety problems than parents of healthy children who were matched in age, gender and IQ (Skokauskas et al, 2012). Therefore, support for parents should incorporate knowledge about the delay of adaptive functioning in children with PWS and the consequences in daily life.…”
Section: Results In Relation To Previous Researchmentioning
confidence: 98%
“…There was also a recognition by the mothers of inappropriate parenting practices. Wulffaert and colleagues in a study on maternal stress in families with children who have PWS reported that professional support is essential for families because of the high stress levels found in the mothers of those with the syndrome 20.…”
Section: Management Of Childmentioning
confidence: 99%
“…Parents and caregivers of people with PWS are routinely faced with two types of problems; the control of access to food to avoid and/or minimize other health problems (such as obesity, scoliosis, and cardiovascular and endocrine illnesses) 12 , and family burden, especially on the primary caregiver, due to the difficulties in the management of behavioral problems that start from early childhood 13,14,15 . Although scientific evidence has shown the neurobiological basis of the behavioral changes and patterns of hyperphagia, interventions which involve giving guidance to parents and caregivers in respect of parenting practices and the management of the children's behavioral problems are considered to be a priority; previous studies report that these interventions can not only improve a range of behavioral indicators in the children but also help support the caregiver in relation to the emotional difficulties they face [16][17][18][19][20][21] . Parents and/or caregivers in general are the main agents of change in any type of behavioral management of their children 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of appetite-satiety patterns may cause obesity (McCune andDriscoll 2005, Dudley et al 2008;Cassidy and Driscoll 2009;Yearwood et al 2011;Miller 2012) which can be potentially life-threatening (Mazaheri et al 2013). Typical behavioural phenotype includes temper tantrums, stubbornness, manipulative, compulsive and oppositional behaviours, aggression, self-injurious behaviour, and sleep abnormalities (Cassidy and Driscoll 2009;Wulffaert, Scholte and Van Berckelaer-Onnes 2010;Cassidy et al 2012). These problems result in lower quality of life (Caliandro et al 2007;Driscoll et al 2014).…”
Section: Introductionmentioning
confidence: 99%